Contribution of TAL effectors in Xanthomonas to diseases of rice and wheat - Peng, Zhao (Kansas State University, 2015)
Rice and wheat are two major crops that suffer losses from the diseases of bacterial blight and bacterial leaf streak, which are caused by Xanthomonas oryzae pv. oryzae (Xoo) and Xanthomonas translucens pv. undulosa (Xtu), respectively. Transcriptional-Activator Like (TAL) effectors, a special family of type III effector proteins from Xanthomonas, have been demonstrated as critical virulence factors that act by inducing corresponding susceptibility (S) genes in several disease complexes of plants. In this study, I analyzed the contributions of TAL effectors from Xoo and Xtu to virulence and in modulating host gene expression to enhance susceptibility. Specifically, the TalC effector from the African Xoo strain AXO1947 was identified as a critical virulence factor, which functions by promoting expression of the gene OsSWEET14 in rice. TalC is interchangeable with other major TAL effectors from Asian strains of Xoo on the basis of functional complementation. The TAL effector PthXo2 from the Asian Xoo strain JXO1 is a major virulence factor and contains 21.5 repeats in the central repetitive region that targets OsSWEET13 in indica rice varieties but not in japonica rice varieties. A one repeat deletion in the PthXo2 effector enabled effector specificity to switch from indica rice to japonica rice. TAL effector genes from a genomic analysis of the Xtu strain XT4699 and related strains were characterized with regards to their involvement in virulence and the modulation of host gene expression in the Chinese Spring wheat cultivar. The identification of TAL effectors with virulence contributions and their target S genes is important for understanding the virulence mechanisms of Xanthomonas bacteria and promises to provide new strategies for disease control.
Keywords: Xanthomonas; Transcriptional activator-like effector; Bacterial blight of rice; Bacterial leaf streak of wheat; Plant Pathology (0480)